A critical study on the translation of thirumurukarrupadai by sir p. Arunachalam - Cumaran, E. (University of Jaffna, 2016)
Translating Tamil works into English or any other Western languages began from the th latter part of the 19 century. Institutionalized education, Western literary influence and the knowledge of Western languages had induced a great number of scholars to indulge themselves in this endeavour both in Sri Lanka and Tamil Nadu. Particularly, in Sri Lanka the reawakening of the Saiva-Tamil movement, championed by Arumuganavalar and his adherents and its counteract against evangelism too kindled the motivation of the scholars to concern about such translations. Sir P. Arunachalam, the brother of renowned Sir P. Ramanathan was being an eminent scholar, educationalist, ardent follower of Saivaism and th the strong advocator of Saiva Tamil Movement in the early decades of 20 Century. He translated Thirumurukarrupadai completely and certain verses sporadically from the Tamil Bhakthi literatures like Thiruvacakam, Thirukkovaiyar and Thayumanavar Padalkal. In this study, the translation of Thirumurukarrupadai is taken into consideration. The objective of this study is to highlight the merit of his translation and identify the techniques and devices applied by him. This study is based on descriptive research methodology and compare study with other translations is also made to evaluate the effectiveness and the accuracy of his translation. Through this study it is possible to comprehend the motivation and the inspiration that led the pioneer translator and learn the techniques and devises applied in the translation of literature which deals with the theme of Bhakthi.
Keywords: Literary translation; Sir P. Arunachalam